Development of a mental health promotion model for the older people by family - Karseewong, wiramon; Kongthanachayopit, Suprawee (Journal of Nursing, Siam University, 2022)
Objective: To study 1) the basic information on the mental health promotion for the older people by families, and 2) to develop the Mental Health Promotion Model for the older people by Families (MHPMOF model). 3) to test the effect of the MHPMOF model. Method and study design: The Research and Development had 3 phases. In phase 1, a qualitative study of basic information on mental health promotion of the older people used the data to develop the MHPMOF model in phase 2 and tested the developed model in phase 3. The study in phase 1 had 2 groups of key informants such as community leaders, caregivers, health workers of 8 persons, and the elderly 8 persons. Phase 2, developing the MHPMOF model used key informants such as community leaders, the elderly, family members, of the elderly, and community health volunteers of 21 persons. Phase3, to develop the MHPMOF model using a quasi-experimental study, the sample was the elderly aged over 60 years including good communication, willing to participate, and had a family caregiver who care for the elderly as 18 persons. Data collecting used elderly mental health assessment (T-GMHA-15). Data were analyzed by paired t-test. Results: The study revealed that the problems and causes of mental health in the elderly's perspective were the elderly having more burdens such as family expenses, debts, and caring for children. There were problems with family communication, chatting with misunderstandings. Four steps in the MHPMOF model were step 1 strengthening family knowledge and understanding. step 2 strengthening family relationships, step 3 empowering and encouragement for the elderly, and step 4 caring for the elderly with love and care. The results of the experiment were the mean mental health scores of the elderly before and after the experiment with difference statistically significant (p < 0.05).The mean score before the experiment was 38.50 (S.D. = 8.35) and after the experiment was 54.11 (S.D. = 6.51), t = 8.166. Conclusion: According to research findings, family is important to the mental health of the elderly, the family should take care of the elderly for having no more burden, well communication with understanding. Because the family is a social institution that is close to the elderly.